2008
DOI: 10.1093/qjmed/hcn159
|View full text |Cite
|
Sign up to set email alerts
|

Readiness exercise to combat avian influenza

Abstract: We recommend the use of case simulation as an effective means of assessing potential breaches in infection control procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…mask 50 % effective) Based on assumptions from previous study Chen et al 2008 [ 33 ] where mask efficacies are assumed to be 60 %, 70 %, 80 %, or 95 % and are combined in the model with other control measures Laboratory data, Lee et al 2008 [ 52 ], and a randomised control trial by Aiello et al 2010 [ 26 ] that found hand hygiene and facemask together were 35-51 % effective but not facemask use alone No data cited for exposure reduction, these are assumptions. Failure rate estimate from a hospital simulation study Seet et al 2009 [ 32 ] Laboratory data from Balazy et al 2006 [ 30 ] used to build particle transmission model Reported none available Reported none available Type of economic evaluation Cost-effectiveness analysis Cost-effectiveness analysis Cost-effectiveness analysis Cost-effectiveness analysis Cost-effectiveness analysis Cost-effectiveness analysis Cost-effectiveness analysis Perspective Policy developer view Not stated Not stated Healthcare institution Not stated Not stated Not stated Primary outcome measure Total costs of intervention Unit cost per person, per year Net savings compared to no intervention Incremental increase in cost per death averted Productivity loss to economy from absenteeism Cost of respirator use per case prevented and per life saved Minimum estimates of cost per life saved and cost per death averted Intervention outcome measures Cases Cases Cases, deaths, hospitalisations Cases, deaths Deaths, hospitalisation, outpatient visits, absenteeism HCW PPD test conversion rates Patients isolated for suspected TB, confirmed cases pulmonary TB in patients and active pulmonary TB in HCWs PPE personal protective equipment, PPD positive protein derivative skin test, TB tuberculosis, HCW healthcare worker, SARS severe acute respiratory syndrome, HEPA high-efficiency particulate air, PARP powered air purifying respirator, DM dust-mist, DMF dust-mist-fume …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…mask 50 % effective) Based on assumptions from previous study Chen et al 2008 [ 33 ] where mask efficacies are assumed to be 60 %, 70 %, 80 %, or 95 % and are combined in the model with other control measures Laboratory data, Lee et al 2008 [ 52 ], and a randomised control trial by Aiello et al 2010 [ 26 ] that found hand hygiene and facemask together were 35-51 % effective but not facemask use alone No data cited for exposure reduction, these are assumptions. Failure rate estimate from a hospital simulation study Seet et al 2009 [ 32 ] Laboratory data from Balazy et al 2006 [ 30 ] used to build particle transmission model Reported none available Reported none available Type of economic evaluation Cost-effectiveness analysis Cost-effectiveness analysis Cost-effectiveness analysis Cost-effectiveness analysis Cost-effectiveness analysis Cost-effectiveness analysis Cost-effectiveness analysis Perspective Policy developer view Not stated Not stated Healthcare institution Not stated Not stated Not stated Primary outcome measure Total costs of intervention Unit cost per person, per year Net savings compared to no intervention Incremental increase in cost per death averted Productivity loss to economy from absenteeism Cost of respirator use per case prevented and per life saved Minimum estimates of cost per life saved and cost per death averted Intervention outcome measures Cases Cases Cases, deaths, hospitalisations Cases, deaths Deaths, hospitalisation, outpatient visits, absenteeism HCW PPD test conversion rates Patients isolated for suspected TB, confirmed cases pulmonary TB in patients and active pulmonary TB in HCWs PPE personal protective equipment, PPD positive protein derivative skin test, TB tuberculosis, HCW healthcare worker, SARS severe acute respiratory syndrome, HEPA high-efficiency particulate air, PARP powered air purifying respirator, DM dust-mist, DMF dust-mist-fume …”
Section: Resultsmentioning
confidence: 99%
“…Dan et al [ 12 ] estimated baseline intervention effectiveness rates of 50, 80 and 90 % as protective equipment (including masks) and isolation precautions were increased. They did not cite data to support these estimates, however a 5 % failure rate where transmission still occurs despite the use of protective equipment and isolation measures, was obtained from a hospital simulation study [ 32 ]. Chen and Liao [ 21 ] applied a relative efficacy estimate of masks in combination with other control measures which was developed in a previous modelling study that did not cite supporting data for efficacy input assumptions [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Multivariate sensitivity analysis was performed to understand the impact of viral characteristics as well as different hospital response policies on cost-effectiveness outcomes. The number of persons exposed in hospital and protective gear failure rates were from an actual outbreak simulation exercise performed at our hospital ( 12 ). Because there were no cases of pandemic (H1N1) 2009 virus infections during this period, estimates were all based on those in the literature ( 13 ).…”
Section: Methodsmentioning
confidence: 99%
“…in response to SARS-CoV-2 (n = 117, 79.1%). [6][7][8] Eighteen were motivated by Ebola outbreaks (12.2%), [129][130][131][132][133][134][135][136][137][138][139][140][141][142][143][144][145][146] 7 by influenza (4.7%), [147][148][149][150][151][152][153] 3 by MERS (2%), [154][155][156] and 3 by pandemics in general (2%). [157][158][159] Regarding the types of simulation-based research, 130 studies assessed the efficacy of simulation as a training methodology (87.8%) and 18 used simulation as an investigative methodology (12.2%).…”
Section: Study Selectionmentioning
confidence: 99%